Assessing content validity of students’ self-efficacy scale in the context of Massive Open Online Course (MOOC) - Ghazali, Norliza; Nordin, Mohamad Sahari; Hashim, Sulaiman; Hussien, Suhailah; Mohd Ayub, Ahmad Fauzi (Majlis e-Pembelajaran IPTA Malaysia, Ministry of Education, 2018)
This study aimed to measure the content validity of students’ self-efficacy scale in the context of Massive Open Online Course (MOOC). MOOC is a new innovation in web-based distance learning program which posed a great challenge to the traditional classroom teaching mode and it is also an alternative way of delivering interactive teaching and learning (Ministry of Education Malaysia)